Social Network Analysis in the Dissemination of Makan Bergizi Gratis (MBG) Program Information on Social Media X - Nadinta Rafifah Suaib; Desna Aryana Pratiwi (Asosiasi Dosen Muda Indonesia, 2025)
The presence of social media encourages users to be more active in interacting and voicing opinions related to news that is in the spotlight. One notable example is the Makan Bergizi Gratis (MBG) program. The purpose of this study is to identify the social networks formed in the conversations of social media users discussing the Makan Bergizi Gratis (MBG) program. A quantitative approach using the Social Network Analysis (SNA) method was employed to address the research question. The findings indicate that social networks on social media X specifically discuss this program. Geraldd434543 and GenZNusantara are the primary actors with the highest degree of centrality and eigenvector centrality values in the network. A total of 297 nodes demonstrate a closeness centrality value, indicating that these actors are closely connected within the network. The network lacks actors who serve as brokers or intermediaries, based on the centrality values observed.